Comparative characteristics of systems Anti-money laundering and combating the financing of terrorism mechanisms Republic of Kazakhstan and Russian Federation (Journal of Economic Research & Business Administration, 2023)
The research topic is related to the comparative analysis of the mechanisms of functioning of AML/CFT systems of the Russian Federation and the Republic of Kazakhstan.The object of the study is the mechanisms of functioning of the "Countering money laundering and terrorist financing" AML/CFT systems of the Russian Federation and the Republic of Kazakhstan in terms of identifying and reducing the risks of money laundering and terrorist financing of ML/FT. The subject of the study is a set of economic relations related to the functioning of the national AML/CFT systems of the Russian Federation and the Republic of Kazakhstan to identify and reduce the risks of money laundering and terrorist financing of ML/FT. The purpose of the study is to conduct a comparative analysis of the mechanisms of functioning of the "Countering money laundering and terrorist financing" AML/CFT systems of the Russian Federation and the Republic of Kazakhstan.   The purpose of the study is to analyze and compare the mechanisms of functioning of the "Countering Money laundering and terrorist financing" AML/CFT of the Russian Federation and the Republic of Kazakhstan.Results of the work - for the first time a comparative analysis was carried out and problem areas of AML/CFT systems of the Russian Federation and the Republic of Kazakhstan were identified.The value of the conducted research is to contribute to the further development and improvement of the national financial monitoring system of the Republic of Kazakhstan by identifying inconsistencies in the AML/CFT systems of the two countries and determining the points of their convergence and harmonization.Practical significance - the results of the comparative analysis will contribute to taking into account the current problems and prospects for the development of national AML/CFT systems of the Russian Federation and the Republic of Kazakhstan, will assist in eliminating the shortcomings inherent in these systems in terms of identifying and reducing the risks of ML/FT.Keywords: financial intelligence, financial monitoring, money laundering, AML/CFT systemKeywords: financial intelligence, financial monitoring, money laundering, AML/CFT system